THE INFLUENCE OF HUMAN RESOURCE QUALITY AND WORK PROFESSIONALISM ON EMPLOYEE PERFORMANCE IN DISTRICT PUBLIC WORKS AND SPATIAL PLANNING DEPARTMENT KAMPAR: Indonesia - Yolanda Herman Nita; Goddess Deswimar (Yayasan Wayan Marwan Pulungan, 2024)
This research aims to determine the partial and simultaneous influence between the quality of human resources and work professionalism on employee performance in the public works department and spatial planning of Kampar district. The sampling technique was carried out using the Slovin technique. The sample used in this research was all ASN employees in the Kampar Regency public works and spatial planning department, namely 109 people. This research is quantitative and descriptive using multiple linear regression testing tools and using the SPSS V.27 data processing program. This research, based on the t-test carried out, shows that the human resources quality variable (X1) has a partially positive and significant effect on employee performance (Y), and Work Professionalism (X2) has a partially positive and significant effect on employee performance (Y). Through the F test, it is known that together the independent variables affect the dependent variable